Pharmacogenomic considerations in opioid analgesia. [Corrigendum] - Vuilleumier PH; Stamer UM; Landau R (Dove Medical Press, 2013)
Vuilleumier PH, Stamer UM, Landau R. Pharmacogenomic considerations in opioid analgesia. Pharmacogenomics and Personalized Medicine. 2012;5:73–87.The authors regret an error in their Figure 1, CYP metabolism involved in opioid clearance. Read the original article